PP No. 10 tahun 1983 dan SE No. 08/SE/1983 tentang izin perkawinan dan perceraian bagi pegawai negeri sipil serta petunjuk pelaksanaan - INDONESIA._[UNDANG_UNDANG,Peraturan_dsb.] (Ghalia Indonesia, 1985)
oen, c.1/ir,c.2-6/stoc3=c.2-6